Control of adipose tissue lipoprotein lipase expression by isoproterenol - Halimah Abdullah Sani, (Universiti Kebangsaan Malaysia, 1996)
Isoproterenol decreased adipose tissue lipoprotein lipase (LPL) activity during in vitro incubation and the decrease was dose-dependent. The activity was reduced to 54.5% of the control (P<0.001) by 10 µM isoproterenol after 2h incubation. Isoproterenol did not alter general protein synthesis, LPL synthesis or relative LPL synthesis. It has no significant effect on general protein degradation but significantly increased LPL degradation. The percentage of LPL degradation was increase from 39.8% in the absence to 54.2% in the presence of 10 µM isoproterenol. The level of LPL mRNA as well as the ratio of LPL mRNA/α-tubulin mRNA were significantly decreased by 23% (P<0.05) during 2h incubation at 32°C. These results show that the control of adipose tissue LPL expression by isoproterenol occurred at the level of transcription and posttranslation.